Contribution of contrasting plant hierarchies to the response to N fertilizer in maize - Caviglia, Octavio Pedro (2011)
The typical size structuring process that occurs as a consequence of intra-specific competition in maize promotes the appearance of contrasting plant hierarchies (i.e. dominated and dominant individuals). This process may become more intense under low nitrogen (N) availability. The alleviation of plant competition by N addition may reduce plant yield variability through a differential response to N in individuals of contrasting hierarchies. In this work, the response to N of dominated and dominant plants from stands with contrasting N supply (0 to 140-200kgNha-1) was examined on 11 experiments carried out in Paraná, Argentina (31°50'S; 60°31'W) in a broad range of growing conditions that included the variation of the year, genotype, plant population and sowing date. Our objectives were: (i) to evaluate the response to N in contrasting plant hierarchies of maize, (ii) to quantify the contribution of dominated and dominant plants to the response to N of the overall stand, and (iii) to study the effect of N on relationships between plant hierarchies and stand variability. Response to N of yield per plant was associated with biomass per plant in non-fertilized controls, tending to be higher in plants with low biomass. The response to N of yield per unit area (i.e., considering all individuals of the stand) was related to the response to N of dominant and dominated plants (P<0.0001). However, at a higher level of response to N of grain yield per unit area (>50-60%), dominant plants had a considerable lower response than dominated plants, whereas at a lower level of response (<30%), the contribution of contrasting plant hierarchies was similar. In stands with similar plant biomass between hierarchies, the differences in the response to N between plant types tended to be negligible. The coefficient of variation of yield per plant was reduced (P<0.05) by effect of N in 4 out of 11 experiments, although it tended to be consistently lower in fertilized treatments. When the differences between the biomass of dominated and dominant plants were ample we found the highest response to N at the stand level, as a result of the higher increase in grain yield per plant in dominated plants than in dominant ones. The response to N in each plant hierarchy was differentially associated with increases in shoot biomass, harvest index, kernel number per plant and kernel weight.